Strategic marketing for social enterprises in developing nations - Chiweshe, Nigel, 1983-; Ellis, Debbie, 1967- (Business Science Reference, an imprint of IGI Global, 2019)
"This book provides insights into the marketing of social enterprises from a developing state perspective as these communities are usually the ones afflicted with massive social challenges not as prevalent in developed states. It also contains practical guides to the marketing of social enterprises to ultimately provide social improvement"--